Budidaya Udang Vannamei (Litopenaeus vannamei) dengan Sistem Intensif Terhadap Pertumbuhan, Kelangsungan Hidup dan Feed Conversion Ratio - Akbarurrasyid, Muhammad; Prajayati, Vini Taru Febriani; Astiyani, Wahyu Puji; Nurkamalia, Ilma (Fakultas Perikanan dan Kelautan Universitas Riau, 2023)
Intensive vannamei shrimp cultivation is a high-density culture to get maximum results with the use of limited cultivation space. High cultivation activities cause high waste production, which inhibits growth, survival rate, and feed conversion ratio (FCR). This study aims to determine the cultivation of vannamei shrimp with an intensive system on growth, survival rate, and FCR. The research was carried out in Legok Jawa, Pangandaran in the period March–May 2022. The research was carried out by means of a survey and analyzed by a quantitative descriptive approach. The results of the study obtained growth values, namely: Mean Body Weight (MBW) ranges from 1.61 to 21.11 g/head, Average Daily Growth (ADG) ranges from 0.14 to 0.62 g/day, size is 49 fish/kg and biomass is 7,680 kg. The survival rate value obtained is around 95.07 – 84.87%, while the feed conversion ratio (FCR) value ranges from 1.2 to 1.5. In general, the results of growth, survival rate, and FCR showed high performance and supported the success of vannamei shrimp culture with intensive systems.